The Effect of EDM Die-sinking Parameters on Non-conductive Materials - Md Ali, Mohd Amran; Laily, Suraya; Nor Assyura, Nor; Hussein, Nur Izan Syahriah; Muhamad, Mohd Razali; Manshoor, Mohd Bukhari; Lajis, Mohd Amri (2014)
The machining ability of electrical discharge machining (EDM) die-sinking on acrylic as non-conductive material was studied. The objective of the study is to establish a new setup to machine a non-conductive material by using EDM die-sinking. Acrylic plastic material was selected as to represent the other groups of non-conductive materials. The experiment was conducted using a ischarge sinking machine with copper as the tool electrode. Metal insert as conductive material was plug-in into acrylic workpiece. Polarity of the setup was set to positive at the copper electrode and negative at the plug-in metal insert. The variable input parameters such as electric discharge current, voltage, pulse on time and pulse off time had been observed to review machinibility of diesinking EDM by taking the overcut and taper of sidewall of holes produced. It was found that the highest current supply during machining, the deepest hole occurred on the acrylic workpiece. Thus, the new method purposed on this study proved that non-conductive material can be machined using the EDM die-sinking.